معاينة أثر التغيير التنظيمي على الأداء الوظيفي لدى العاملين بالإدارة العامة لجامعة المرقب (دراسة ميدانية) (Comprehensive Journal of Science, 2025)
This study aims to identify the impact of organizational change on the job performance of employees in the General Administration at Al-Marqab University. To achieve this, the researcher developed a questionnaire as a tool for collecting primary data. Due to the small size of the population, the study followed a comprehensive survey method for all components of the population. The survey was distributed to the study population, which consisted of department and office managers, heads of departments and units at the university, totaling (65) employees. The researcher used a descriptive approach in this study, which aims to describe the phenomenon and analyze data related to the study variables. Some statistical methods were also used in selecting the study hypotheses. The results showed that all dimensions of organizational change were high, with structural change ranking first, followed by technical change, followed by behavioral change. There is also a strong correlation and a statistically significant moral effect of the dimensions of organizational change as independent variables on employee job performance, as a dependent variable in the level of job performance of employees in the institution. Based on the results reached by the study, recommendations were made, including working to enhance interest in the dimension of structural change, especially with regard to setting agreed-upon standards that demonstrate the extent of the need for organizational change, and paying attention to discussing all ideas. Concerns about change, particularly individuals' belief that the current management situation is better than the new one, lead to resistance to organizational change. Emphasis is placed on allocating sufficient financial facilities to obtain modern technology and high-quality techniques to promote technological change. Despite the high level of employee performance, greater attention is needed to develop a more detailed guide to job performance in university administration that helps employees improve their job performance.